Exploring the possibilities of transhumanistic risk management - Vorontsova, Yu. V.; Gil Martínez, M. A. (UPRAVLENIE / MANAGEMENT (Russia), 2023)
The article considers the actual reflection of the transhumanistic concept in various fields of scientific knowledge. This concept has recently aroused genuine interest both because of its direction and because of its own contradictions. The discussion that has unfolded around this concept allows to evaluate all the pros and cons of the implementation of the transhumanist idea, which requires improving the physical condition of a person through the use of the most advanced technologies, among which biotechnology occupies an important place. Their use generates contextual social, economic and political problems. In this regard, it is necessary to investigate the process of emergence and development of transhumanistic risks, as well as the possibility of managing them on the basis of both traditional and original tools, taking into account the specifics of the transhumanistic approach. In the article, the authors present a study of the formation of transhumanistic risks associated with the creation and use of artificial intelligence, as well as the possibility of risk management in the transhumanistic space. The threat is increasing due to the growing globalization, interconnectedness and the speed of change in the world. These trends are generally useful, but present new challenges, including new types of transhumanistic risks associated with the use of artificial intelligence. It is more difficult to predict them than any other known risks. Conceptual options for assessing the situation developing in the transhumanistic space together represent a new vector transhumanistic risk management theory and practice development.